2014
DOI: 10.1111/jgh.12795
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori infection with healthy subjects in Japan

Abstract: Background and Aim: Only few large-scale epidemiological studies have examined the prevalence of Helicobacter pylori (H. pylori) infection in Japan. The aim of the present study was to estimate the prevalence and incidence of H. pylori infection in Japan in terms of gender, age and region. Methods: Serum anti-H. pylori antibody testing was included in workers' annual health checks conducted by T-company's health insurance association in 2008. The testing was continued for the next 5 years in 35-year-old subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 15 publications
4
47
1
Order By: Relevance
“…At a time when the H. pylori infection rate is decreasing in Japan, we showed here an infection rate in 500 patients receiving hemodialysis of 15.0%, which is significantly lower than the current rate in healthy Japanese individuals (37.4% in the sixth decade and 46.1% in the seventh decade in 2014) [16] or in hemodialysis patients in a worldwide meta-analysis (43.9%) [27] reported in 2011. In addition, we demonstrated that H. pylori infection in 19.6% patients receiving hemodialysis was considered to be naturally eradicated, although they had no specific treatment history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a time when the H. pylori infection rate is decreasing in Japan, we showed here an infection rate in 500 patients receiving hemodialysis of 15.0%, which is significantly lower than the current rate in healthy Japanese individuals (37.4% in the sixth decade and 46.1% in the seventh decade in 2014) [16] or in hemodialysis patients in a worldwide meta-analysis (43.9%) [27] reported in 2011. In addition, we demonstrated that H. pylori infection in 19.6% patients receiving hemodialysis was considered to be naturally eradicated, although they had no specific treatment history.…”
Section: Discussionmentioning
confidence: 99%
“…A recent large-scale Japanese epidemiological study showed that the infection rate has declined to 30-50%, especially in younger patients [16]. The prevalence of H. pylori infection in patients receiving dialysis has been investigated, and in most studies, the infection rate in patients with chronic kidney disease receiving continuous ambulatory peritoneal dialysis (CAPD) and hemodialysis is shown to be equal to or lower than that in subjects with normal renal function in various population groups [17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50% of the world population are infected with H. pylori; however, the rate of infection is variable among countries: for example, the infection rate is 62% in China, 27.5% in Japan, 65.6% in Vietnam, and 45.9% in Thailand (Shi et al, 2008;Nguyen et al, 2010;Hirayama et al, 2014;Uchida et al, 2015). Metronidazole (Mtz) is a standard triple therapy recommended by the 1994 National Institute of Health Consensus for H. pylori eradication (NIH Consensus Development Panel on Helicobacter pylori in Peptic Ulcer Disease, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…While the prevalence of Helicobacter pylori (H. pylori) has been decreasing [1,2], it remains a critical public health issue. Recently, increasing prevalence of CAM-resistant H. pylori is an emerging problem of public health all over the world as CAM is included in most first-line empiric H. pylori eradication regimens [3,4].…”
Section: Introductionmentioning
confidence: 99%